1986
DOI: 10.1007/bf01907934
|View full text |Cite
|
Sign up to set email alerts
|

Human C7 polymorphism: Classification and association analysis with C6

Abstract: SummaryPolymorphism of the seventh component of human complement (C7) was investigated in Japanese. Four common and one rare allotypes were observed with desialized samples. Besides three common alleles, C7"1, C7"2 and C7"4, the existence of the hypomorphic variant, C7"3, was confirmed in Japanese with a polymorphic frequency. The recently described C7"5 was found to correspond to C7"3 by comparing with reference samples. Moreover, a rare variant, tentatively named C7 7, was considered to be new. The populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…A similar observation was made by Nishimukai and Tamaki (1986) and Washio et al (1986) using an immunoblotting procedure for the detection of C7 banding patterns.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…A similar observation was made by Nishimukai and Tamaki (1986) and Washio et al (1986) using an immunoblotting procedure for the detection of C7 banding patterns.…”
Section: Introductionsupporting
confidence: 75%
“…Previous studies on C7 polymorphism suggested that C7 3 might be a 'hypomorphic' variant (Hobart et al, 1978;Nishimukai and Tamaki 1986;Washio et al, 1986). Our present investigation demonstrates that both the immunochemical and functional C7 levels for C7 3-1 are lower than those for the other common phenotypes.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations